Effect of Tryptophan on Growth and Morphology of Hansenula schneggii Cells - Sundhagul, Malee (1966)
Sundhagul, Malee (Illinois Institute of Technology, Chicago), and L. R. Hedrick. Effect of tryptophan on growth and morphology of Hansenula schneggii cells. J. Bacteriol. 92:241–249. 1966.—When Hansenula schneggii cells were cultured aerobically in a tryptophan-glucose medium, 70 to 90% of the cells were elongated; no growth occurred under anaerobic conditions. The size of the elongated cells was 15 to 25 μ by 2 to 4 μ, as compared with 2.5 to 5 μ for ellipsoidal cells. Formation of elongated cells occurred essentially during the logarithmic growth period; the highest percentage of elongated cells was found soon after the end of this growth phase. In the later stationary phase, some of the cells formed spherical buds which became spherical cells. The rate of cell division during this period was greatly reduced, but the spherical cells formed decreased the percentage of elongated cells in the population. Cells cultured in a membrane-filter filtrate of a tryptophan-glucose medium (with limiting tryptophan), in which elongated cells had been grown, were ellipsoidal until nitrogenous nutrients were exhausted; thereafter the cells were elongated if tryptophan was added. Of compounds related to tryptophan, kynurenine was the only one which induced a high percentage of the cells to elongate. Some amino acids, such as cystine, histidine, phenylalanine, tyrosine, and threonine, induced elongation in about 15% of the cells. Growth of cells with other amino acids, or the addition of most of the other amino acids to tryptophan-glucose medium, resulted in a population of spherical cells. Several consecutive sequential transfers of cells into tryptophan medium induced elongation in 90% of the cells, but one transfer from a culture with elongated cells into a medium with ammonium sulfate, or a mixture of amino acids, gave a culture with ellipsoidal cells. Growth in media at pH 4 or 5 favored formation of elongated cells; as the pH was increased, the percentage of elongated cells decreased. Carbon sources other than glucose did not affect the percentage of elongated cells, except for the alcohols mannitol and erythitol, which gave comparable growth but reduced the percentage of elongated cells from 70 to 50%. Cell wall analyses of the two types of cells indicated that elongated cells have 2.5 times as much mannan as cell walls of ellipsoidal cells. This suggests that tryptophan, kynurenine, and, to a limited extent, some of the other amino acids cause a diversion of polysaccharide biosynthesis to mannan in the elongated cells rather than to glucan as in ellipsoidal cells.